Potensi Gulma Rorippa indica Sebagai Reservoar Parasitoid Hemiptarsinus varicornis untuk Mengendalikan Liriomyza huidobrensis - Hamdani, Hamdani; Nuryanti, Ni Siluh Putu (Jurnal Penelitian Pertanian Terapan, 2011)
Leafminers, Liriomyza huidobrensis (Blanchard) (Diptera: Agromyzidae) known as main pest at vegetable and ornamental crop. Hemiptarsinus varicornis (Girault) (Hymenoptera: Eulophidae) is one of ectoparasitoid larvae of L. huidobrensis that usually find in the field, however the levels of parasitism at field relative lower. Therefore we need the conservation technology of parasitoid in order to its population overflow so that its performance increases. Rorippa indica (L) have potential as reservoir of parasitoid H. varicornis, so that can be used as conservation medium of H. varicornis. Planting weeds R. indica among of chickpea crop, can decraese the population of adult and larvae L. huidobrensis significantly, increase adult population H. varicornis and larvae population L. huidobrensis parasitism by H. varicornis. Growth rate of population adult H. varicornis at block without weeds R. indica follow the pattern of regretion equation Y=0,1312X?0,2246 and Y=0,7172X+1,1 while at the block planted weeds R. indica. Growth rate of larvae population L. huidobrensis at block without weeds R. indica follow the pattern of regretion equation Y=0,9315X?0,9835 and Y=0,8647X+1,0875 while at the block planted weeds R. indica. Weeds R. indica can be used as reservoar parasitoid H. varicornis in the effort the conservation parasitoid. Keywords: Biological control, Leafminer, Liriomyza huidobrensis, conservation technology reservoir parasitoids, Hemiptarsinus varicornis